KEGAGALAN REFORMASI EKONOMI RUSIA DI ERA BORIS YELTSIN (1991-1999) - , R.RICO DWI N. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This undergraduate thesis tries to assess the process of Russiaâs economy reformation, in order to explain itâs transition from socialist-centralized to liberalism-free market system under President Boris Yeltsin (1991-1999). By using neo-liberalism perspective, it analyses how Russia has merged into world economics after the collapse of Soviet Union. Russia chose to comply the recommendation from International Monetary Fund (IMF), known as Washington Consensus which contains three main pillars: liberalization, privatization, and deregulation. These Structural Adjustment Programes (SAPs) injected by the IMFâs led Russia to economic crisis and failures, ranging from larger debt, poverty, to oligarch corruption in private sector.